Aggregate-Depleted Brain Fails to Induce Aβ Deposition in a Mouse Model of Alzheimer's Disease - Duran-Aniotz, Claudia; Morales, Rodrigo; Moreno-Gonzalez, Ines; Hu, Ping Ping; Fedynyshyn, Joseph; Soto, Claudio (PloS one, 2014)
Recent studies in animal models of Alzheimer's disease (AD) show that amyloid-beta (Aβ) misfolding can be transmissible; however, the mechanisms by which this process occurs have not been fully explored. The goal of this study was to analyze whether depletion of aggregates from an AD brain suppresses its in vivo "seeding" capability. Removal of aggregates was performed by using the Aggregate Specific Reagent 1 (ASR1) compound which has been previously described to specifically bind misfolded species. Our results show that pre-treatment with ASR1-coupled magnetic beads reduces the in vivo misfolding inducing capability of an AD brain extract. These findings shed light respect to the active principle responsible for the prion-like spreading of Alzheimer's amyloid pathology and open the possibility of using seeds-capturing reagents as a promising target for AD treatment.